(untitled) (Research, Society and Development, 2021)
Aging is a phenomenon that has happened all over the world, resulting in an increase in the number of elderly people, who are considered to be people over 60 years of age. With this fact, there has been an increase in chronic conditions, accompanied in the scope of oral health by a considerable tooth loss. Therefore, the aim of this study was to carry out an integrative literature review in order to analyze the local and systemic, physiological and pathological factors that influence tooth loss. Thus, a search was conducted on the PUBMED, LILACS and SCIELO websites. Once the inclusion and exclusion criteria were established, at the end, two articles were selected for discussion of the most relevant methodological resources and findings. It could be observed in this search that most studies are literature reviews on the most diverse themes and that some research found emphasize some specific factor. Therefore, it is known that tooth loss is still a reality in the elderly today and that these public needs preventive care in order to maintain oral and systemic health and ensure an adequate quality of life.